Authentic assessment in Studio-Based Learning (SBL) e-Portfolio / Syamsul Nor Azlan Mohamad, Siti Nur Dini Mahazan and Siti Zuraida Maaruf - Mohamad, Syamsul Nor Azlan; Mahazan, Siti Nur Dini; Maaruf, Siti Zuraida (UiTM Press, 2021)
This article takes an in-depth look at the rationale behind the integrating e-Portfolio as an authentic assessment in studio-based learning in higher education institutions (HEIs) which could impact the performance of the studio learners in professional development. In the field of studio based learning (SBL), the studio learning system is comprehensive as it combines theoretical and practical knowledge which covers various disciplines. Learning in the studio field through a complex iterative process involves collecting, processing, analysis, translation, synthesis, design and delivery of a project or an artwork. Therefore, the complexity of assessment in the field of studio-based learning (SBL) such as architecture, art and design require attention and supervision because of its very subjective nature, which is whether to focus on the process, the student or the product. In order to achieve this target, authentic assessment is used as a measurement tool for studio students to identify the level of job evaluation, performance and progress through e-Portfolio. Literature reviews have been conducted in order to carry out the goal of this article. The results of studies mostly shows a positive attitude towards the use of e-Portfolio as an authentic assessment for learning in the studio-based field. Therefore, this study recommends implementation of e-Portfolio as a platform for studio learners so that studio learners can easily view their assessment regarding the evaluation of their work, performance and progress.